2014
DOI: 10.3389/fpubh.2014.00063
|View full text |Cite
|
Sign up to set email alerts
|

Wind Turbines and Human Health

Abstract: The association between wind turbines and health effects is highly debated. Some argue that reported health effects are related to wind turbine operation [electromagnetic fields (EMF), shadow flicker, audible noise, low-frequency noise, infrasound]. Others suggest that when turbines are sited correctly, effects are more likely attributable to a number of subjective variables that result in an annoyed/stressed state. In this review, we provide a bibliographic-like summary and analysis of the science around this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 69 publications
0
37
0
1
Order By: Relevance
“…Annoyance from wind turbine sound 5.2.1 Some studies have correlated turbine sound with annoyance, which may be associated with sleep disturbance, negative emotions, or other health-related effects (Knopper & Ollson, 2011;Knopper et al, 2014;Michaud et al, 2016a). The annoyance experienced by people living near utility-scale wind facilities is correlated to more negative attitudes (Fast et al, 2016;Firestone et al, 2015).…”
Section: Sound Annoyance and Health Risk Perceptionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Annoyance from wind turbine sound 5.2.1 Some studies have correlated turbine sound with annoyance, which may be associated with sleep disturbance, negative emotions, or other health-related effects (Knopper & Ollson, 2011;Knopper et al, 2014;Michaud et al, 2016a). The annoyance experienced by people living near utility-scale wind facilities is correlated to more negative attitudes (Fast et al, 2016;Firestone et al, 2015).…”
Section: Sound Annoyance and Health Risk Perceptionsmentioning
confidence: 99%
“…Some research has demonstrated that annoyance and complaints decline with increased distance from turbines (Kaliski & Neeraj, 2013;Nissenbaum et al, 2012), but there is no general consensus about the setback distance required to minimize or mitigate annoyance (Nissenbaum et al, 2012) as distance is just one component of how sound from turbines propagates to nearby residents. Accordingly, researchers (and stakeholders in general) often rely on a sound-specific threshold to reduce annoyance and stress impacts and concerns from local residents, which is commonly 40-45 dBA 6 (Knopper & Ollson, 2011;Knopper et al, 2014;Paller, 2014;Phadke, 2013 . In a recent comprehensive study of measured wind turbine sound levels and reported health effects, turbine noise reached a maximum of 46 dBA and a mean of 35.6 dBA for 1,238 residents living between 0.25 -11.22 kilometers from operational wind turbines in Canada (Michaud et al, 2016b).…”
Section: Sound Annoyance and Health Risk Perceptionsmentioning
confidence: 99%
See 3 more Smart Citations